DIFFERENTIATION TREND AND PARENT MELT COMPOSITION OF NI-BEARING GABBRO-WEHRLITE PECHENGA INTRUSIONS, KOLA PENINSULA - Latypov R.M.; Smolkin V.F.; Alapieti T.T. (My University, 2001)
The geologic section of the widely known Pechenga intrusions with accompanying nickeliferous mineralization consists of the following three principal zones (listed in order from bottom to top): wehrlite, clinopyroxenite, and gabbro. It is commonly believed that this succession of zones corresponds to the following crystallization sequence of silicates: Ol → Ol + Cpx → Cpx + Pl (Smolkin, 1974, 1977a; Marakushev et al., 1986; Hanski, 1992). This crystallization succession implies olivine disappearance in the absence of peritectic reactions between olivine and any of the phases. To settle this problem, we performed an additional petrological investigation of the Pilgujarvi intrusion, the largest in the Pechenga group, in which relict primary magmatic assemblages are preserved. The rocks of the gabbro zone were determined to pervasively contain serpentine-chlorite pseudomorphs after olivine, a fact suggesting that olivine crystallization did not stop in the upper portion of the intrusion. Hence, the actual differentiation trend of the nickeliferous Pechenga intrusions corresponds to one of the theoretically possible crystallization trends of basaltic magma within the volume of the Ol-Cpx-Pl-Qtz phase diagram: Ol → Ol + Cpx → Ol + Cpx + Pl (Irvine, 1970). The composition of the parent melt of nickeliferous intrusions is traditionally inferred from the weighted mean composition of the intrusion or the composition of its lower chill zones. However, practically all of the intrusive rocks were metamorphosed under greenstone-facies conditions, and, hence, the direct use of their chemical analyses faces certain obstacles. The best compatibility with the established differentiation trend is shown by the compositions calculated from the quantitative mineralogical compositions of the rocks and the actual chemistry of their rock-forming, accessory, and ore minerals.